Use of Claim-Evidence Reasoning Method in Schools to Enhance Women's Empowerment in Research - Swati A Shinge; Seema Kiran Bhandare (International Journal of Education Sciences, 2025)
Although today's women are literate, their level of science literacy is very low. If we want to increase the participation of women in research in the future, it should be implemented at the school level. Claim Evidence Reasoning is an effective method of teaching, that will help the students understand the concepts of science easily, build scientific literacy among them, increase their confidence, and increase their participation in research, which will definitely help in women's empowerment. Increasing scientific literacy among women will go a long way in their overall development and empowerment. Therefore, emphasis should be placed on making science education more effective at the school level, so that women's research participation increases and society progresses. This paper has conducted a comprehensive study on how the progress of students due to teaching through the claim evidence reasoning method will contribute to women's empowerment. The study also looks at the relationship between young women's development of critical thinking abilities—which are crucial for creativity and research—and better scientific comprehension. The study also shows how gender barriers in science-related sectors can be broken down by early exposure to good teaching methods, opening the door for equitable chances and long-term societal development.
Keywords: Claim Evidence Reasoning (CER); Scientific Literacy; Teaching Methodology; student engagement; women empowerment